Isolated Facial Nerve Palsy in Childhood Acute Myeloid Leukemia - Hafiz, MG; Islam, A; Mannan, MA; Rahman, F (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Case report-1: Sabarna, a female baby of fifteen months old was admitted in Pediatric Hematology and Oncology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh with the complaints of deviation of the angle of mouth to right side and inability to close the left eye for five days. Systemic examination revealed an incision scar mark on the left mastoid region. Facial asymmetry as evidenced by smooth forehead, absence of nasolabial fold, drooping of the angle of mouth and nonclosure of eyelid on left side. She was mildly pale, mild hepatomegaly, no lymphadenopathy, bone pain or bleeding manifestation. Physical, hematological and histopathological investigations the features were suggestive of facial nerve palsy due to granulocytic sarcoma (GS) with acute myeloid leukemia (AML). Following second day of chemotherapy her vital signs suddenly deteriorated and succumbed probably due to the leukostasis or intracranial hemorrhage. Case report-2: Chayon, another nine month old female baby was admitted in the same unit with the history of fever, proptosis of both eye balls, deviation of the angle of mouth to the right side and unable to close the left eye for one month. Physical examination revealed facial asymmetry with the features of left sided facial nerve palsy along with proptosis of eyeballs. She was moderately pale, moderate hepatosplenomegaly, no bleeding manifestation or bone pain. Physical, hematological and cerebrospinal fluid (CSF) examination the features were suggestive of facial nerve palsy due to leukemic cell infiltration with AML. Following induction and consolidation the baby is on continuation phase with regular follow up for last 9 month having significant improvement of her facial nerve palsy along with hematological remission. DOI: 10.3329/jbcps.v28i1.4646 J Bangladesh Coll Phys Surg 2010; 28: 53-58